The wisdom literature - Clifford, Richard J. (Nashville, TN : Abingdon, 1998)
In this volume, Richard J. Clifford seeks to make the biblical wisdom literature intelligible to modern readers. It is easy to quote the occasional proverb, say a few things about "the problem of evil" in Job, or quote "vanity of vanities," but far more rewarding to read the whole book with an appreciative and informed eye. Opening chapters of The Wisdom Literature comment on the striking similarities between ancient and modern "wisdom literature" and on the comparable literature from ancient Mesopotamia, Egypt, and Canaan. Thereafter, a chapter is devoted to each biblical book (Proverbs, Job, Ecclesiastes, Song of Songs, Sirach, and Wisdom of Solomon), studying not only its content but also its rhetoric - how it engages the reader.
includes bibliographical references and indexes.
Keywords: Bible. -- criticism, interpretation, etc